Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0192079
|View full text |Cite
|
Sign up to set email alerts
|

Standardization and reference ranges for whole blood platelet function measurements using a flow cytometric platelet activation test

Abstract: IntroductionPlatelet function testing with flow cytometry has additional value to existing platelet function testing for diagnosing bleeding disorders, monitoring anti-platelet therapy, transfusion medicine and prediction of thrombosis. The major challenge is to use this technique as a diagnostic test. The aim of this study is to standardize preparation, optimization and validation of the test kit and to determine reference values in a population of 129 healthy individuals.MethodsPlatelet function tests with 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…High degrees of inter-individual variability were previously observed for the platelet response to agonists (particularly ADP) and anti-platelet drugs [48][49][50][51]; this was also observed in the present study. Therefore, the effect of AR agonists on platelet aggregation was evaluated in high-and low-responders to P2Y 12 inhibitors using aggregometry: a simple method which allows rapid assessment of platelet response.…”
Section: Discussionsupporting
confidence: 88%
“…High degrees of inter-individual variability were previously observed for the platelet response to agonists (particularly ADP) and anti-platelet drugs [48][49][50][51]; this was also observed in the present study. Therefore, the effect of AR agonists on platelet aggregation was evaluated in high-and low-responders to P2Y 12 inhibitors using aggregometry: a simple method which allows rapid assessment of platelet response.…”
Section: Discussionsupporting
confidence: 88%
“…All samples were analysed on a FACS Canto flow cytometer (BD Biosciences, Franklin Lakes, NJ, USA). The CVs of platelet function are below 10% for all platelet activation measurements, except ADP‐induced P‐selection expression, which has a CV below 20% …”
Section: Methodsmentioning
confidence: 87%
“…However, it has been shown, especially in aggregometry assays, that factors such as gender and race in healthy subjects may affect platelet function results [45]. A study aimed at evaluating the reference intervals of flow cytometry-based platelet function results found that ADP-induced platelet activation was significantly higher in females than males [112]. On the contrary, some studies have demonstrated no significant antiplatelet effect in hypertensive populations [93,94,96] (Table 1).…”
Section: Evaluation Of Methods Used For Polyphenol Antiplatelet Studiesmentioning
confidence: 99%